Communicating Sustainability Through Performing Arts: A Case Study of Teater Koma In Indonesia - Cobis, Mikhael Yulius; Ronda, Andi Mirza; Ikhsano, Andre (Jurnal Toursci, 2025)
Background. Sustainable communication has gained prominence as society tackles social resilience, cultural preservation, and climate change. Numerous studies have investigated environmental groups, business strategies, and media campaigns; however, few have analyzed sustainable communication within the performing arts, especially theater. Teater Koma is a prestigious theater group in Indonesia, and this study seeks to examine the comprehension and dissemination of sustainability among cultural institutions. Aims. This study investigates, through the lens of sustainability communication, (1) Teater Koma members’ concerns about sustainability practices, (2) sustainability communication both internally and externally, and (3) challenges related to acceptance and implementation. Methods. Data was gathered via a qualitative case study, incorporating participant observation, document analysis, and comprehensive interviews. The research indicates that Teater Koma incorporates sustainability into resource management, stage design, intergenerational values, cultural resilience, and narrative strategies. Conclusion. This research enhances the literature on sustainability communication by integrating performance studies with environmental and organizational communication studies. Implementation. It offers Southeast Asian ideas, where the interplay between tradition, modernization, and ecological responsibility is intricately interwoven.